2018
DOI: 10.1111/ppa.12929
|View full text |Cite
|
Sign up to set email alerts
|

Trichothecene production is detrimental to early root colonization by Fusarium culmorum and F. graminearum in fusarium crown and root rot of wheat

Abstract: Fusarium culmorum (Fc) and F. graminearum (Fg) belong to the predominant causal agents of fusarium crown and root rot (FCR) in wheat. While many studies have been done to investigate crown rot, including stem base infection, root colonization and mycotoxin production associated with root rot is not well understood. In this study the impact of mycotoxins on the colonization of wheat roots and stem bases was analysed by using Fc and Fg isolates that varied in both quantity and types of trichothecenes they produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Correlations between DON and its acetylated forms were highly significant, which is in accordance with the previous research (Sunic et al, 2021), where DON highly correlated with 3-AcDON in winter wheat, and its production by F. culmorum is believed to play a role in pathogenesis (Morimura et al, 2020). Mycotoxin accumulation affects germination rates, seedling growth, pathogen aggressiveness, and overall disease severity (Bruins et al, 1993;Scherm et al, 2011;Winter et al, 2019). Scherm et al (2011) showed that DON is an aggressiveness factor in F. culmorum stem base infections of durum wheat, whereby disease incidence was decreased by 40%−80% when the trichothecene regulatory gene Tri6 was silenced (Scherm et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Correlations between DON and its acetylated forms were highly significant, which is in accordance with the previous research (Sunic et al, 2021), where DON highly correlated with 3-AcDON in winter wheat, and its production by F. culmorum is believed to play a role in pathogenesis (Morimura et al, 2020). Mycotoxin accumulation affects germination rates, seedling growth, pathogen aggressiveness, and overall disease severity (Bruins et al, 1993;Scherm et al, 2011;Winter et al, 2019). Scherm et al (2011) showed that DON is an aggressiveness factor in F. culmorum stem base infections of durum wheat, whereby disease incidence was decreased by 40%−80% when the trichothecene regulatory gene Tri6 was silenced (Scherm et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…We determined that the genus Fusarium was significantly enriched in RSD treatment as a common pathogenic fungus ( Steinkellner and Langer, 2004 ). The enrichment of Fusarium may lead to the occurrence of wheat root diseases and damage of wheat root surface (M. Winter et al, 2019 ), which may be more conducive to the parasitism of P. graminis on wheat roots (K. Hansen et al, 2013 ; Mestre and Fontenla, 2021 ). In conclusion, the occurrence of Wheat yellow mosaic virus disease affects the composition of soil fungal community, but there are many reasons for this change, such as soil physicochemical interaction and soil nutrient imbalance (C.H.…”
Section: Discussionmentioning
confidence: 99%
“…We determined that N.fusarium was signi cantly enriched in RSD treatment as a common pathogenic fungus (S SteinkellnerI Langer, 2004). The enrichment of Fusarium may lead to the occurrence of wheat root diseases and damage of wheat root surface (M Winter, 2019), which may be more conducive to the parasitism of P.graminearum on wheat roots (K Hansen, 2013; MC MestreS Fontenla, 2021). In conclusion, the occurrence of Wheat yellow Mosaic virus disease affects the composition of soil fungal community, but there are many reasons for this change, such as soil physicochemical interaction and soil nutrient imbalance (CH Kong, 2008; C Li, 2010), may also be due to the promoting or inhibiting effect of plant rhizosphere exudates on the growth of different fungal communities (X-g Li, 2014a), more detailed reasons need to be explored.…”
Section: Discussionmentioning
confidence: 99%